Significant differences in cardiopulmonary and metabolic load of guided vs. Unguided low-intensity rowing in elite athletes - Winkert, K.; Alimoradinasrabadi, B.; Treff, G.; Steinacker, J. M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Elite rowers spent about 11 hours/week with specific endurance training in the boat, with low-intensity training being the main component. As external intensity metrics like boat velocity are highly dependent on environmental conditions and power meters are missing, athletes and coaches rely mainly on internal metrics like heart rate (HR) and rating of perceived exertion (RPE). While in the context of optimal training stimulus management adequate pacing during daily training is needed, athletes tend to over pace during LIT. Therefore, we aimed to evaluate differences in cardiopulmonary (CP) and metabolic (MB) load of guided vs. unguided rowing at three LIT zones in elite rowers. METHODS: Fifteen elite male and female rowers (age 23 ±3/23 ±2 years, body mass 82.6 ±6.5/74.6 ±8.4 kg, maximal oxygen consumption (*O2max) 75.3 ±4.0/63.5 ±2.5 ml/min/kg) completed one laboratory test and four on-water session. Laboratory tests included an ergometer ramp test to determine *O2max and HRmax. On-water sessions in the single scull consisted of two unguided and two guided trials of six 15-minute stages, separated by 24 hours. During the unguided trials, the rowers were instructed to row two self-paced consecutive stages each, in a compensation zone (zone1), a lower (zone 2.1), and an upper (zone2.2) basic endurance zone, according to their usual RPE. The guided sessions were based on specific rates of HRmax, being 60-72% zone 1, 72-79% zone 2.1, and 79-82% zone 2.2. CP and MB load were determined continuously using a portable metabolic analyzer in dynamic mixing chamber mode. Blood lactate concentration (BL) and RPE were determined after each stage. Mean values with 95% confidence intervals (95%CI) were calculated based on the *O2 steady-state phase of each stage. Inter-mode differences were calculated based on a linear mixed model approach. RESULTS: Differences in CP and MB load for guided vs. unguided rowing in zone 1/zone 2.1/zone2.2 amounting to %HRmax *3.2% 95%CI [*4.5; *1.8]/*2.9% 95%CI [*4.0; *1.8]/*3.2% 95%CI [*4.1; *2.3]; %VO2max *3.5% 95%CI[*5.1; *1.9]/*1,9% 95%CI [*3.2; *0.6]/*1.9% 95%CI [*3.1; *0.8]; BL *0.1 mmol/l 95%CI [*0.1; 0.0]/*0.2 mmol/l 95%CI [*0.3; *0.1]/*0,5 mmol/l 95%CI [*0.6; *0.3] and RPE *0.1 95%CI [*0.3; 0.1]/*0.1 95%CI [*0.4; 0.1]/*0.3 95%CI [*0.6, *0.0], respectively. Besides BL in zone 1 and RPE in zone 1, 2.1 there were significant differences for all metrics in all zones between guided vs. unguided trials. CONCLUSION: While RPE ratings between guided and unguided on-water training in the single scull were similar, CP and MB loads were significantly higher during unguided trials. Therefore, even elite rowers tend to underestimate the intensity of their self-paced rowing training compared to CP and MB load. This might lead to a mismanagement in total training load and risk of maladaptations. Consequently, external guidance like HR in combination with RPE should be used for precise intensity management during on-water rowing.